The Influence of Service Quality and Iron Drum Product Quality on Customer Satisfaction in the Diamond Iron Drum Trading Business in Tangerang Regency - Saiba Sabilillah; Ibnu Haris; Muhamad Nurman (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The increasingly competitive industrial world demands that companies maintain product and service quality to maintain customer satisfaction. In the chemical industry, the use of iron drums plays a crucial role as containers for storing and transporting various chemicals and industrial fluids. Therefore, the quality of the iron drum product and the quality of the service provided to customers are factors that can influence customer satisfaction levels. This study aims to analyze the influence of service quality and product quality on customer satisfaction at the Intan Drum Trading Business in Tangerang Regency. This study uses a quantitative approach, and the results of this study indicate that product quality also has a positive and significant effect on customer satisfaction, with product quality being the variable that has the most dominant influence compared to service quality.